Estudio de la sostenibilidad financiera en las cooperativas de ahorro y crédito del segmento uno - Rengel Herrera, Karla Estefanía (2023)
The objective of this research work was to analyze the sustainability financial study in the saving and credit cooperatives that belongs to one segment in Loja city, it was applied a quantity methodology through the vertical and horizontal analysis of the financial statements, and the application of the sustainability evaluation model proposed by Tuckman, the same that contains four dimensions. The population study, was formed for six saving and credit cooperatives of the one segment which operates in Loja city. The discovered results show us that the financial structure of the evaluating cooperatives does not present significant problems. When we apply the Tuckman model, we can notice that during the period 2019-2021, the 29 de Octubre, Pequeña Empresa Pastaza, Jardín Azuayo, Policía Nacional, Vicentina Manuel Esteban Godoy and Juventud Ecuatoriana Progresista Saving and Credit Cooperatives were sustainable concerning their patrimony. According to the income dimension, the six studied cooperatives are in the quintiles one and two. While, in refrence with the operating operating margin, the financial identities that operate and manage their financial resources are Pequeña Empresa Pastaza, Jardin Azuayo, and Vicentina Manuel Esteban Godoy Saving and Credit Cooperatives. In addition, regarding to the Administrative Expense Dimension, the 29 de Octubre Pequeña Empresa Pastaza, Jardín Azuayo, Policía Nacional, Vicentina Manuel Esteban Godoy, and Juventud Ecuatoriana Progresista ,saving and Credit Cooperatives are the ones that are maintained at the long term and have managed their expenses more adequately. Finally, it developed a composite index to measure and prioritize the sustainable financial level of the evaluated cooperatives.